Cultural heritage – right, identity and dignity - Rakić, Branko (Sociološki pregled, 2021)
In international human rights law established after World War Two, one of cultural rights that has been traditionally most neglected out of five categories of human rights (civil, political, economic, social and cultural rights), is the right to participation in cultural life, while its segment, by the nature of things, is also the right of access to and enjoyment of cultural heritage. Although international human rights law thus establishes the basis for treating the right of access to and enjoyment of cultural heritage as a human right, international acts dealing with the matters of cultural heritage protection have had a long-prevailing approach in which cultural goods were protected because of their inherent value. It was only recently, with the emerging needs and interests in respect of the safeguarding of cultural diversity and protection of intangible cultural heritage, that the emphasis began to be placed on the relationship, including the legal one, between cultural heritage and human communities, groups and individuals with a special subjective attitude towards it. That is how the human-rights based system of cultural heritage protection was gradually established and the segment of international law dealing with human rights was brought closer to the segment dealing with cultural heritage. In order to consider a right as a human right, apart from the will of law-makers to be like that, it also requires the existence of certain values which constitute the basis for it and which should be safeguarded through the protection of that human right. An understanding deriving from a series of international legal acts and being widespread in theory is that, when it comes to cultural rights, including the right of access to and enjoyment of cultural heritage, such basis is constituted by identity, first of all cultural identity, and human dignity. Therefore, although the foundation is laid for the right of access to and enjoyment of cultural heritage to be treated as a human right, it is necessary to clarify and elaborate, at the legal level, a number of questions which should ensure effective enjoyment of this right. The task is in the hands of states, either as participants in the adoption of international law acts or as national law-makers, so the question remains open as to the nature of their attitude to further development of the human-rights based system of cultural heritage protection.